Improving ambulance care for children suffering acute pain: a qualitative interview study - Gregory Adam Whitley; Pippa Hemingway; Graham Richard Law; Aloysius Niroshan Siriwardena (BMC Emergency Medicine, 2022)
Abstract Background Pain is a highly complex sensory and emotional experience. When a child suffers acute pain through illness or injury, they are often transported to hospital by ambulance. Pre-hospital pain management in children is poor, with 61% of children receiving suboptimal pain management. Consequences of poor pain management include the risk of developing post-traumatic stress disorder and altered pain perception. We aimed to identify clinicians’ perceptions of barriers, facilitators and potential improvements for the management of pre-hospital acute pain in children. Methods Qualitative face to face semi-structured recorded interviews were performed in one large UK ambulance service. Audio files were transcribed verbatim with thematic analysis used to generate themes. NVivo 12 was used to support data analysis. Findings were combined with existing evidence to generate a driver diagram. Results Twelve ambulance clinicians participated, including 9 registered paramedics and 3 emergency medical technicians. Median (IQR) age was 43.50 (41.50, 45.75) years, 58% were male, median (IQR) experience was 12 (4.25, 15.50) years and 58% were parents. Several themes relating to barriers and facilitators were identified, including physical, emotional, social, organisational, environmental, management, knowledge and experience. Improvement themes were identified relating to management, organisation and education. These data were combined to create a driver diagram; the three primary drivers were 1) explore methods to increase rates of analgesic administration, including utilising intranasal or inhaled routes; 2) reduce fear and anxiety in children, by using child friendly uniform, additional non-pharmacological techniques and more public interaction and 3) reduce fear and anxiety in clinicians, by enhancing training and optimising crew mix. Conclusions The quality of care that children receive for acute pain in the ambulance service may be improved by increasing rates of analgesic administration and reducing the fear and anxiety experienced by children and clinicians. Future research involving children and parents would be useful to determine the most important outcome measures and facilitate intervention development.